(Contro)storia e satira politica: su Storia di domani di Curzio Malaparte - Bruni, Raoul (Załącznik Kulturoznawczy, 2021)
Storia di Domani (1949) is one of Curzio Malaparte’s most original and unclassifiable works. In some ways this novel can be considered an ‘uchronia’, given that it is based on an alternative historical hypothesis: the invasion of Europe by the Soviet Union in the aftermath of the Second World War. On the other hand, the novel is similar to the genre of political fiction, given that the characters are mostly real Italian politicians who were still alive at the time the work was published. The article will focus on the interweaving of historical memory, political satire and literary fiction, showing how Malaparte’s book had anticipated in many ways more recent and better-known counterfactual novels such as Morselli’s Contro-Passato Prossimo and Biancardi’s Aprire il Fuoco.